In: Computer Science
Prove the validity using laws of propositional logic and rules of inference:
∀x(P(x) → (Q(x) ∧ S(x)))
∃x(P(x) ∧ R(x))
− − − − − − − − − − − − −
∴ ∃x(R(x) ∧ S(x))
given
∀x(P(x) → (Q(x) ∧ S(x)))
∃x(P(x) ∧ R(x))
Step | Reason |
1. ∃x(P(x) ∧ R(x)) | Hypothesis |
2. P(a) ^ R(a) | Existencial instantiation from (1) |
3. P(a) | Simplification from (2) |
4. ∀x(P(x) → (Q(x) ∧ S(x))) | Hypothesis |
5. P(a) -> (Q(a) ^ S(a)) | Universal instantiation from (4) |
6. (Q(a) ^ S(a)) | Modus ponens from (3) and (5) |
7. R(a) | Simplification from (2) |
8. R(a) ^ Q(a) ^ S(a) | Conjunction from (6) and (7) |
9. ∃x(R(x) ∧ S(x)) | Existential generalization from(8) |